Efficacy of Caffeine in ADCY5‐Related Dyskinesia: A Retrospective Study. Issue 6 (5th April 2022) - Méneret, Aurélie; Mohammad, Shekeeb S.; Cif, Laura; Doummar, Diane; DeGusmao, Claudio; Anheim, Mathieu; Barth, Magalie; Damier, Philippe; Demonceau, Nathalie; Friedman, Jennifer; Gallea, Cécile; Gras, Domitille; et al.
Abstract: Background: ADCY5 ‐related dyskinesia is characterized by early‐onset movement disorders. There is currently no validated treatment, but anecdotal clinical reports and biological hypotheses suggest efficacy of caffeine. Objective: The aim is to obtain further insight into the efficacy and safety of caffeine in patients with ADCY5 ‐related dyskinesia. Methods: A retrospective study was conducted worldwide in 30 patients with a proven ADCY5 mutation who had tried or were taking caffeine for dyskinesia. Disease characteristics and treatment responses were assessed through a questionnaire. Results: Caffeine was overall well tolerated, even in children, and 87% of patients reported a clear improvement. Caffeine reduced the frequency and duration of paroxysmal movement disorders but also improved baseline movement disorders and some other motor and nonmotor features, with consistent quality‐of‐life improvement. Three patients reported worsening. Conclusion: Our findings suggest that caffeine should be considered as a first‐line therapeutic option in ADCY5 ‐related dyskinesia. © 2022 International Parkinson and Movement Disorder Society Abstract : ADCY5 ‐related dyskinesia is characterized by early‐onset movement disorders due to hyperactivity of adenylate cyclase type 5, an enzyme likely inhibited by caffeine, in the striatum. In this retrospective study, caffeine was well tolerated, and 87% of 30 patients reported a clear clinical and quality‐of‐life improvement.